(untitled) (Proceedings of Faculty of Civil Engineering, 2022)
Expressions for the Euler’s critical load at which buckling of straight slender rods occurs can be derived by solving the differential equation of the elastic curve of the beam under the assumption of small displacements and rotations. As this procedure does not allow one to obtain the elastic curve of the rod after buckling takes place, in this work geometrically nonlinear theory is used for determining equilibrium states in the post-critical phase with the corresponding axial load. In order to verify the theoretical predictions, two experiments of buckling of a slender flexible rod were performed with optical measurements of rod’s displacements. Experiments have shown that the theoretical model can very accurately predict the deformed shape of the rod and the corresponding value of the axial load.